Influência do agente radiopacificador na solubilidade, no pH e na ação antimicrobiana do cimento Portland - Machado, Adriano Cosme de Oliveira (2011)
To evaluate the interference of the association of different radiopacifier agents (bismuth oxide, bismuth carbonate, zirconium oxide and bismuth subnitrate) on solubility, in the pH and antimicrobial activity of Portland cement. The ratio of the materials was in volume, at a ratio of 4 parts of Portland cement and 1 part of radiopacifiers. The analysis of the solubility complied with ADA's standards n.57. In the analysis of pH, the materials were placed in acrylic teeth with retrograde cavities, and immersed in vial containing Milli Q Water and at the end of 3, 24, 72 and 168 hours of manipulation, the teeth were removed to another vial and the water in which they were immersed the pH was measured with a pHmeter. To analyze the antimicrobial action the radial diffusion test was performed using microorganisms: Staphylococcus aureus (ATCC 25923), Pseudomonas aeruginosa (ATCC 27853), Enterococcus faecalis (ATCC 29212) and Candida albicans (ATCC 10231). The analysis of the presence and size of the antimicrobial active zones was performed 24 hours after the inoculation of microorganisms and the placing of materials in the pits. In the solubility, the adding of bismuth subnitrate and bismuth carbonate conferred greater solubility to Portland cement, raising levels above the maximum recommended by the ADA s standard which is 3%. The results showed for the pH, that all the materials alkalinized the mean which, in the 3 hours analysis the bismuth subnitrate favored significantly a lower pH than the pure Portland cement. However, in the 24 and 72 hours analysis the adding of bismuth subnitrate gave higher pH values, but without differentiating the pure Portland cement. By at the end of 7 days the materials showed similarity in pH values. In the analysis of the antimicrobial action, all materials showed action against to Candida albicans, and the largest antimicrobial active zones was when it was added the zirconium oxide, which differed statistically (P <0.05) from other materials. Regarding other organisms, none of the materials tested showed antimicrobial action. The overall radiopacifiers did not interfere in the pH and antimicrobial action of Portland cement and the bismuth carbonate and bismuth subnitrate made the material more soluble.